Nutrition Literacy and Healthy Diet: Findings from the Validation of a Short Seniors-Oriented Screening Tool, the Spanish Myths-NL - Elena Lobo (MDPI AG, 2021)
A good level of nutrition literacy (NL) is proposed as a determinant factor for following a healthy diet. Improving seniors’ NL might be particularly pertinent to enhance the quality of their diets. This study aimed to systematically design and validate a short seniors-oriented questionnaire as a screening tool to evaluate NL. We developed the Myths-NL questionnaire, composed of 10 widespread nutrition myths, and checked for its content and face validity. An observational cross-sectional study was conducted to explore the validity and the test–retest reliability, involving a community-dwelling group of 316 individuals aged 65 years and over. Construct validity was proved by establishing both discriminant and convergent validity. Cronbach α = 0.61 and Spearman r = 0.79 (p = 0.02) demonstrated internal consistency and test–retest reliability. Participants who had secondary/university studies scored significantly higher compared with those with primary (p < 0.001), and a significant linear relationship (R2 = 0.044, p = 0.001) with a positive slope (β = 0.209) between Mediterranean Diet Adherence Screener (MEDAS) and Myths-NL scores was observed, proving construct validity. In conclusion, the Myths-NL questionnaire is a valid and reliable tool to screen NL in Spanish seniors and it might be useful as an assessment NL tool for designing and implementing lifestyle interventions to promote healthy eating.